2020
DOI: 10.1097/jom.0000000000002109
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infections Among Healthcare Personnel in the United States Veterans Health Administration, March to August, 2020

Abstract: Objective: We investigated COVID-19 infection and death among healthcare personnel (HCP) in the United States Veterans Health Administration. Methods: HCP with positive Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) reverse transcription polymerase chain reaction tests between March 1 and August 31, 2020 were included. Risk ratios were calculated for sex, age, race/ethnicity, Veteran status, occupation category, facility of employment by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 12 publications
2
21
0
2
Order By: Relevance
“…Among these hospitalized HCW, 28% of these patients were admitted to an intensive care unit, 16% required invasive mechanical ventilation, and 4% died [ 1 ]. A 4.5% positivity was noted out of 131,606 United States HCW who were tested at 1225 Veterans Health Administration medical centers between 12 February and 16 July 2020; however, this total may be an underestimation [ 2 ]. When personal protective equipment (PPE) is adequate, available, and properly used, infection rates of COVID-19 among HCW drop below those reported rates among the general public [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these hospitalized HCW, 28% of these patients were admitted to an intensive care unit, 16% required invasive mechanical ventilation, and 4% died [ 1 ]. A 4.5% positivity was noted out of 131,606 United States HCW who were tested at 1225 Veterans Health Administration medical centers between 12 February and 16 July 2020; however, this total may be an underestimation [ 2 ]. When personal protective equipment (PPE) is adequate, available, and properly used, infection rates of COVID-19 among HCW drop below those reported rates among the general public [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of increased SARS-CoV-2 infections among HCP worldwide since the beginning of the pandemic. 5 , 6 , 7 , 8 In a large prospective cohort study of over 2 million community individuals and nearly 100,000 HCP in the UK and USA, HCP were found to have a 3.4 times increased risk of SARS-CoV-2 infection compared to the general population. 6 Several SARS-CoV-2 outbreaks amongst healthcare workers have also been reported and directly linked to a single index patient, often a patient with a delayed diagnosis of COVID-19 due to negative tests early in the hospital course.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In the US, nursing staff have been shown to have higher COVID-19 rates and associated hospitalizations compared to other HCP; other clinical HCP also had higher rates compared to non-clinical support and infrastructure personnel. 7 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…21 Regarding health workers, a recent study reported a 0.3% death rate and a 4.5% positivity rate in Veterans Administration health workers. 22 In time, the Occupational Health and Safety Administration (OSHA) can be expected to clarify morbidity and mortality associated with the pandemic with publicly available data. However, at present, only a patchwork of reference group death rate data is available and estimates likely will change in time.…”
Section: Benchmark One: Targeted Testing and Random Surveillance By Rt-qpcrmentioning
confidence: 99%